Analysis of the Job Creation Act (UUCK) Mandate Through Government Regulation Number 18 of 2021 - Wibowo, Arif Tri; Kinanggi, Dzulhidayah (Sekolah Tinggi Pertanahan Nasional, 2022)
Agrarian conflicts occur from legal politics in the land sector, where the rules issued by the government are not compatible or contradictory. The Job Creation Act (UUCK) provides convenience in various regulatory aspects such as in the land sector, one of the implementing regulations is Government Regulation no. 18 of 2021. This study focuses more on analyzing with the intention to show a comparison of regulations that have been issued before and after the Job Creation Act as a regulation arrangement in the land sector through Government Regulation No. 18 Year 2021. The author uses a qualitative method through a statute approach by collecting data and information and interpreting matters relating to relevant objects to draw conclusions. The results of the analysis show that the Job Creation Act has produced implementing regulations for at least 5 (five) government regulations in the land sector to cut previous regulations and reorganize regulations. Government Regulation No. 18 of 2021 provides new scope arrangements such as arrangements for Right to Manage (HPL), Land Reclamation, Land Destroyed, Space Above Land (RAT) and Underground Space (RBT). Government Regulation No. 18 of 2021 cut overlapping regulations in the land sector so that in their implementation, they can be aligned according to objectives by prioritizing the interests of the wider community and minimizing agrarian conflicts. However, the birth of Government Regulation No. 18 of 2021 raises problems and does not refer to the Basic Agrarian Law as a special law.